Text-Based Instruction: Leveraging Mobile Media to Enhance EFL Learners’ Paragraph Writing Performance - Suharno, Yusak; Wijayatiningsih, Testiana Deni; Purnomo, Eko Andy; Lestariningsih, Enny Dwi (Language Circle: Journal of Language and Literature, 2024)
This study investigates the efficacy of mobile media in enhancing students' paragraph writing skills, motivation, and behavioural involvement. This research seeks to reconcile traditional pedagogical approaches with students' digital practices amid the swift incorporation of technological devices in education. A quasi-experimental approach comprised two groups: an experimental group employing mobile-based media and a control group using conventional methods. Data were gathered via writing evaluations, motivating surveys, and classroom observations. The findings indicate that students in the experimental group exhibited considerably enhanced writing performance compared to the control group. Furthermore, their motivation and behavioural involvement are heightened owing to mobile media's interactive and accessible characteristics. The results indicate that mobile media effectively enhances student-centred learning and encourages active engagement in writing activities. This study emphasizes mobile media's capacity to revolutionize writing instruction and stimulate future pedagogical advancements.